Nutritional Supplementation for Pregnant Women to Prevent Stunting Among Children: A Scoping Review - Nastiti Purbandini; Laili Rahayuwati; Iqbal Pramukti (Universitas Aisyah Pringsewu, 2023)
Stunting can interfere with the growth and development of children because it’s a chronic nutritional problem caused by a deficit in nutritional intake for a long period of time. If during pregnancy the mother's nutritional status is low, there is a risk of giving birth to a stunting baby. Supplements are given to meet the nutritional needs of pregnant women who are not fulfilled from food. Objective: This study aims to analyze the current literature on nutritional supplementation programs for pregnant women to prevent further stunting among children. Methods: This literature review was carried out on articles in PubMed and CINAHL, published from 2012 to 2022, with a systematic review, meta-analysis, as well as clinical and RCT designs in English. The primary keyword used were “supplements” AND “pregnancy” OR “antenatal” AND “stunting” AND “prevention”. Results: Only 9 articles aligned with the criteria were reported, some of which stated that lipid-based nutritional supplements reduced the risk of stunting babies. Furthermore, supplements containing folic acid, iron, micronutrients, zinc, osteocalcin, and animal protein can reduce the risk of stunting. Conclusions: Supplements for pregnant women containing folic acid and iron, specific nutrients, lipid-based nutritional supplements, micronutrients, osteocalcin, and animal protein reduce stunting in children. Abstrak: Stunting dapat mengganggu pertumbuhan dan perkembangan anak karena merupakan masalah gizi kronis yang disebabkan oleh kekurangan asupan gizi dalam jangka waktu yang lama. Jika selama hamil status gizi ibu rendah maka berisiko melahirkan bayi stunting. Suplemen diberikan untuk memenuhi kebutuhan gizi ibu hamil yang tidak tercukupi dari makanan. Penelitian ini bertujuan untuk menganalisis literatur terkini tentang program suplementasi gizi bagi ibu hamil untuk mencegah stunting lebih lanjut pada anak. Tinjauan literatur ini dilakukan pada artikel di PubMed dan CINAHL, diterbitkan dari tahun 2012 hingga 2022, dengan tinjauan sistematis, meta-analisis, serta desain klinis dan RCT dalam bahasa Inggris. Kata kunci utama yang digunakan adalah “suplemen” DAN “kehamilan” ATAU “antenatal” DAN “stunting” DAN “pencegahan”. Hasil: Hanya 9 artikel yang sesuai dengan kriteria yang dilaporkan, beberapa di antaranya menyatakan bahwa suplemen nutrisi berbasis lipid menurunkan risiko bayi stunting. Selain itu, suplemen yang mengandung asam folat, zat besi, mikronutrien, seng, osteokalsin, dan protein hewani dapat menurunkan risiko stunting. Kesimpulan: Suplemen ibu hamil yang mengandung asam folat dan zat besi, nutrisi spesifik, suplemen nutrisi berbasis lipid, mikronutrien, osteokalsin, dan protein hewani menurunkan stunting pada anak.